2022
DOI: 10.3847/1538-4357/ac75cd
|View full text |Cite
|
Sign up to set email alerts
|

Sun-as-a-star Analysis of Hα Spectra of a Solar Flare Observed by SMART/SDDI: Time Evolution of Red Asymmetry and Line Broadening

Abstract: Stellar flares sometimes show red/blue asymmetries of the Hα line, which can indicate chromospheric dynamics and prominence activations. However, the origin of asymmetries is not completely understood. For a deeper understanding of stellar data, we performed a Sun-as-a-star analysis of Hα line profiles of an M4.2-class solar flare showing dominant emissions from flare ribbons by using the data of the Solar Dynamics Doppler Imager on board the Solar Magnetic Activity Research Telescope at the Hida Observatory. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 65 publications
6
23
0
Order By: Relevance
“…The time evolution of the ∆EW Hα±3.0 Å is similar to the GOES SXR light curve; for example, their time scales are comparable in each of the impulsive rising and gradual decay phases and their peaks are almost simultaneous [Figure 4 (b)]. The similarity of the Hα and the GOES SXR light curves is also reported in the Sun-as-a-star analysis of a flare by Namekata et al (2022c). Figure 6 shows the result of the Sun-as-a-star analysis of the Hα spectra of this M8.1 flare.…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…The time evolution of the ∆EW Hα±3.0 Å is similar to the GOES SXR light curve; for example, their time scales are comparable in each of the impulsive rising and gradual decay phases and their peaks are almost simultaneous [Figure 4 (b)]. The similarity of the Hα and the GOES SXR light curves is also reported in the Sun-as-a-star analysis of a flare by Namekata et al (2022c). Figure 6 shows the result of the Sun-as-a-star analysis of the Hα spectra of this M8.1 flare.…”
Section: Resultssupporting
confidence: 70%
“…(i) Flares (≥ C8.0) show emission near the Hα line center, with red asymmetry and/or line broadening in their Sun-as-a-star Hα spectra. Namekata et al (2022c) also reported that the Sun-as-a-star Hα spectrum of an M4.2 solar flare near the disk center showed red asymmetry and line broadening, and they thus suggested that the nature of the chromospheric condensation can be seen even in the Sun-as-a-star spectra. We note that, although event (2) and event (3) are especially energetic events in our study, red asymmetry is not very clear in them.…”
Section: Summary and Implications To Stellar Observationsmentioning
confidence: 95%
See 1 more Smart Citation
“…Since both solar and stellar spectra have similar characteristics, the authors concluded that a stellar filament eruption associated with a superflare had been detected. In addition, Namekata et al (2022c) analyzed the Sun-as-a-star Hα spectrum of an M-class solar flare that exhibited dominant emission from flare ribbons, and they showed that red asymmetry and line broadening can be seen even in a Sunas-a-star spectrum, providing evidence of chromospheric condensation. This is how Sun-as-a-star analyses of Hα spectra are useful for investigating the dynamics of flares and plasmas on a stellar surface.…”
Section: Introductionmentioning
confidence: 99%
“…So far, Sun-as-a-star analyses of Hα spectra have been performed for only three solar active events (flares and filament eruptions/surges; Namekata et al 2022aNamekata et al , 2022c. In this paper, we report the results of Sun-as-a-star analyses of Hα spectra for various active events on the Sun.…”
Section: Introductionmentioning
confidence: 99%